Influences of parentification and benefit finding on prosocial behavior among typically developing siblings of individuals with autism spectrum disorder. (September 2020) - Beffel, Jenna H.; Nuttall, Amy K.
Highlights: Experiences and perceptions of experiences are important for TDS prosocial behavior. ASD benefit finding is a moderator of TDS prosocial behavior. Parentification predicts TDS prosocial behavior. Abstract: Background: Prior research examining typically developing siblings (TDS) of individuals with Autism Spectrum Disorder (ASD) reports both higher and lower levels of prosocial behavior among TDS. TDS' experiences (parent-focused parentification, sibling-focused parentification) and perceptions of experiences (ASD benefit finding, role benefit finding) may interact to influence TDS prosocial behavior. Aims: 1) Examine influences of TDS' experiences and perceptions of TDS experiences on prosocial behavior and 2) examine interactions between TDS' experiences of parentification and perceptions of experiences influencing prosocial behavior while controlling for the Broad Autism Phenotype (BAP). Methods and procedures: TDS [ N = 108; M ( SD ) age = 20.37(1.55)] were college students who reported having a sibling with ASD, defined as "Autism Spectrum Disorder", "Autism", "Asperger's", and "Pervasive Developmental Disability". TDS completed an online survey about their experiences and perceptions of experiences. Outcomes and results: Controlling for gender and BAP, there was a significant interaction between ASD benefit finding and sibling-focused parentification such that at low levels of ASD benefit finding, sibling-focused parentification negatively predicted prosocial behavior. Lower BAP scores and female gender were associated with greater levels of prosocial behavior. Conclusions and implications: TDS experiences and perceptions of experiences are important for understanding TDS prosocial behavior.